Intra-articular therapy with tumor necrosis factor-α antagonists: an update - S. Bello; C. Bonali; L. Serafino; C. Rotondo; N. Terlizzi; G. Lapadula (PAGEPress Publications, 2014)
The aim of the study was to review from the present literature the intra-articular (IA) use of the TNF-blocking drugs. A total of 28 papers about this topic were found through a search in PubMed; the first publication's date was July 2003. These studies include a total of 214 patients affected by 12 different joint diseases that reported a total of 1046 intra-articular therapies carried out in 10 different joint sites. Infliximab and etanercept were the most widely used medications. The safety of this treatment clearly emerges from our analysis, while more difficult was the evaluation of its efficacy. Nevertheless we deduced an ideal patient profile that may better respond to the IA anti-TNF treatment.